دراسة تاريخية للقرآن الكريم: نقط المصحف ومراحله - Hairuddin Hairuddin; Sulaiman Ibrahim (Pascasarjana IAIN Sultan Amai Gorontalo, 2023)
This study aims to reveal one aspect of the historical process of the Qur'an from its revelation to becoming a complete and printed book with varied color patterns which was previously only in the form of plain writing as it appeared in the first centuries. This research uses a descriptive approach, with a literature review method that refers to classical books, Quranic manuscripts, and contemporary research results. The results showed that the renewal of Qur'anic writing went through three stages, namely: the stage of laying syntax points, the placing, and the Mushaf that has been used by Muslims from the early period of the arrival of Islam to the present includes three Mushaf; namely, the plain Mushaf, the dotted Mushaf, and the arithmetic Mushaf. Ibn al-Bawab is considered to be the first person to compile the Quranic harakat format which became the basis for modern Quranic printing.